2018
DOI: 10.1186/s13063-018-2623-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprophylaxis of leprosy with rifampicin in contacts of multibacillary patients: study protocol for a randomized controlled trial

Abstract: BackgroundThe annual new-case detection rate for leprosy, while generally stable over the last decade, shows that transmission rates have remained stagnant despite the successful worldwide administration of multidrug therapy since the 1980s. As such, novel control strategies are urgently needed. Focusing on managing leprosy patient contacts, the most susceptible to contracting the disease, has been seen as a potential strategy in limiting the spread of leprosy as shown by a number of recent epidemiological stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Our findings are therefore compatible with both our previous research as well studies in Brazilian populations. As a pre-emptive approach to reduce the emergence of new cases and enable M. leprae elimination, it has recently been suggested that seropositive individuals that have asymptomatic or sub-clinical M. leprae infection receive BCG re-vaccination as well as treatment with rifampicin to serve as an early intervention to alter the natural course of infection [23, 24]. Our data provide further evidence for the implementation of prophylactic measures within high risk juvenile and other HHC populations.…”
Section: Discussionmentioning
confidence: 58%
“…Our findings are therefore compatible with both our previous research as well studies in Brazilian populations. As a pre-emptive approach to reduce the emergence of new cases and enable M. leprae elimination, it has recently been suggested that seropositive individuals that have asymptomatic or sub-clinical M. leprae infection receive BCG re-vaccination as well as treatment with rifampicin to serve as an early intervention to alter the natural course of infection [23, 24]. Our data provide further evidence for the implementation of prophylactic measures within high risk juvenile and other HHC populations.…”
Section: Discussionmentioning
confidence: 58%
“…Immunoprophylaxis with Bacillus Calmette-Guérin (BCG) is considered an effective preventive measure in the control of the disease due to its ability to stimulate the development of cellular Immunity (27) . The Ministry of Health recommends that BCG be administered in contacts without the presence of signs and symptoms of leprosy and respecting the criteria of vaccination history (15) .…”
Section: Resultsmentioning
confidence: 99%
“…The Ministry of Health recommends that BCG be administered in contacts without the presence of signs and symptoms of leprosy and respecting the criteria of vaccination history (15) . More recently, it has been shown that chemoprophylaxis in a single dose of rifampicin also consists of a promising measure to prevent the disease (27) .…”
Section: Resultsmentioning
confidence: 99%
“…Active search for new cases among household contacts (HHC) is cost-effective since it can detect patients exhibiting early disease stages 5,6 . Large-scale public policies such chemo and/or immunoprophylactic strategies in HHC are effective 79 in decreasing the disease as a public health problem.…”
Section: Introductionmentioning
confidence: 99%